Barriers felt by nurses related to childhood basic immunisation in East Nusa Tenggara: A phenomenological study - Petrus Kanisius Siga Tage; Herliana Monika Azi Djogo (Jurnal Keperawatan Padjadjaran, 2022)
Background: Immunisation barriers can increase morbidity and mortality associated with vaccine-preventable diseases. Understanding barriers to childhood vaccination is critical to informing effective interventions to maximise coverage. Purpose: This study aims to explore the experiences of nurses involved in immunisation related to the obstacles they experience in immunisation activities. Methods: This research is qualitative research with a phenomenological approach. Nurse participants who manage immunisation activities at the public health centre were recruited using a purposive sampling technique. In-depth interviews were conducted with 15 nurses who work in immunisation activities. Inclusion criteria are nurses who directly provide immunisation services and have managed the immunisation program for more than one year. Exclusion criteria were nurses who were on leave. The study was conducted from August to September 2022, and face-to-face interviews were conducted. Interview transcripts were analysed using the thematic analysis method. Results: Three major themes were generated in this study, namely: 1) barriers to immunisation governance systems, 2) barriers to vaccine recipients, and 3) policy barriers. Conclusions: Interventions to overcome barriers to immunisation need to be carried out comprehensively at various levels, such as promoting the benefits of vaccines for the community, strengthening the capacity of officers' competence, reducing political bias, and funding supporting facilities for immunisation programs.